Jackie Robinson [videorecording (DVD)] - Burns, Ken, 1953-; Burns, Sarah, 1982-; David, Keith (PBS, 2016)
Tells of the story of Jack Roosevelt Robinson, a sharecropper's son who elevated an entire race and country when he broke Major League Baseball's color barrier in 1947. The film illuminates Robinson's place as a leader and icon of the civil rights movement whose exemplary life and aspirational message of equality continues to inspire generations of Americans. Includes interviews with family members and rarely-seen photographs and film footage.